PENDETEKSIAN OUTLIER PADA CAPITAL ASSET PRICING MODEL (CAPM) MENGGUNAKAN LEAST TRIMMED SQUARES (LTS) - Elis Ratna Wulan; Enung Nurhayati (JURNAL ISTEK, 2014)
An outlier in the Capital Asset Pricing Model (CAPM) is detected using Least Trimmed Squares (LTS), in order to obtain a robust estimation against outliers without discarding existing data, so it can be considered by investors to make informed decisions in determining the allocation of capital and investment in a company. To detect outlier on the Capital Asset Pricing Model (CAPM) using the Least Trimmed Squares (LTS), Capital Asset Pricing Model (CAPM) to be transformed into a simple linear regression equation.